LIBOR: Origins, economics, crisis, scandal, and reform - David Hou; David Skeie (Federal Reserve Bank of New York, 2014)
The London Interbank Offered Rate (LIBOR) is a widely used indicator of funding conditions in the interbank market. As of 2013, LIBOR underpins more than 300 trillion of financial contracts, including swaps and futures, in addition to trillions more in variable-rate mortgage and student loans. LIBOR's volatile behavior during the financial crisis provoked questions surrounding its credibility. Ongoing regulatory investigations have uncovered misconduct by a number of financial institutions. Policymakers across the globe now face the task of reforming LIBOR in the aftermath of the scandal and crisis.
Keywords: G01; G12; G15; G18; G21; E43; 330; LIBOR; financial crisis; scandal; interbank; banking; reference rate; interest rate